Patients With Reflux Esophagitis Possess a Possible Different Oral Microbiota Compared With Healthy Controls - Wang, Baoyong; Zhang, Yu; Zhao, Qiaofei; Yan, Yifan; Yang, Tian; Xia, Yanli; Chen, Hongwei (Frontiers in Pharmacology, 2020)
Background and Aim Reflux Esophagitis (RE) is caused by a variety of factors including anatomical and functional alterations involved in the pathogenesis. Oral microbiota is influenced by many factors such as heredity, nutrition, environments and host conditions, but little is known about relationship between oral microbiota and RE. The aim of this study was to explore whether the oral microbiota is changed in patients with RE. Methods To clarify this correlation, fresh saliva samples from all subjects were collected and then oral microorganism diversity was analysed in 55 patients with RE and 51 controls via hypervariable tag sequencing and analyzing the V3–V4 region of the 16S rDNA gene. Results There was no difference found in oral microbial diversity between RE patients and healthy controls by Shannon diversity index (p=0.60) and Simpson diversity index (p= 0.38). The abundance of Proteobacteria was lower, but Bacteroidetes was higher in patients with RE at the phylum level. At the genus level the abundances of Prevotella, Veillonella, Megasphaera, Peptostreptococcus, Atopobium, Oribacterium, Eubacterium, and Lachnoanaerobaculum were increased, while Neisseria, Streptococcus, Rothia, Granulicatella, Gemella, Aggregatibacter, Treponema, Campylobacter, Filifactor, Corynebacterium, and Lactivibrio were decreased in RE patients than the controls. Conclusions Our study suggested oral microbial dysbiosis in patients with RE, and identified bacterial species with potential biomarker significance. Further studies are required to understand role of oral microbial dysbiosis in the pathogenesis of RE.